Analysis of noise pollution in an andesite quarry with the use of simulation studies and evaluation indices. Issue 1 (2nd January 2016) - Kosała, Krzysztof; Stępień, Bartłomiej
Abstract : This paper presents the verification of two partial indices proposed for the evaluation of continuous and impulse noise pollution in quarries. These indices, together with the sound power of machines index and the noise hazard index at the workstation, are components of the global index of assessment of noise hazard in the working environment of a quarry. This paper shows the results of acoustic tests carried out in an andesite quarry. Noise generated by machines and from performed blasting works was investigated. On the basis of acoustic measurements carried out in real conditions, the sound power levels of machines and the phenomenon of explosion were determined and, based on the results, three-dimensional models of acoustic noise propagation in the quarry were developed. To assess the degree of noise pollution in the area of the quarry, the continuous and impulse noise indices were used.